2016
DOI: 10.1177/0954406216649404
|View full text |Cite
|
Sign up to set email alerts
|

A new continuously variable transmission system applied to transmission system of the roadheader's cutting unit

Abstract: For the existing roadheader, the transmission system of the cutting unit cannot regulate speed and the cutting motor may break down because of the impact vibration. In this study, the power reflux hydraulic transmission system, which is a new continuous variable transmission system, is put forward to ameliorate these problems. The basic characteristics such as the speed ratio, efficiency and torque ratio are analysed on the basis of expounding the basic structure and operational principle of the power reflux h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 21 publications
0
26
1
Order By: Relevance
“…The solution c has an advantage of energy saving over the schemes proposed in [7,12]. Although the optimal solution c is only verified in the typical operating mode, it can provide an energy saving advantage over the prototype TC in other operating modes as well.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The solution c has an advantage of energy saving over the schemes proposed in [7,12]. Although the optimal solution c is only verified in the typical operating mode, it can provide an energy saving advantage over the prototype TC in other operating modes as well.…”
Section: Discussionmentioning
confidence: 97%
“…A dynamic model for such a transmission was constructed. The simulation results showed that both the vibration of the drive motor and the dynamic engagement force of the gears are substantially lessened compared to those of the prototype transmission when encountering pulse loads [7]. Jo et al suggested a new input torque coupled HMPST concept, where the hydraulic elements were placed at both the mechanical and hydraulic branches.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional method uses the diameter of a circle as the design variable to optimize the matching of the diesel engine and the TC [7][8][9]. However, the transmission performance of PRHTS has changed significantly compared to the prototype TC [10]. The conventional matching method is not applicable to the diesel engine and PRHTS, and it is essential to change the TC parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Boom-type roadheader is the most important equipment in the fully mechanized excavation face, mainly used for excavation of the roadway to prepare the working face for coal mining. Due to the complexity and changeableness of the occurrence condition and physical mechanical properties of coal and rock in roadway cross-section, the hardness of coal and rock during cutting process is changing constantly and randomly; therefore the cutting head load is also continuously changing during the cutting process [7][8][9][10][11][12]. The complex and changeable cutting head load, different dip angles of coal seam, and constantly changing horizontal swing angle of cutting arm cause constant change of roadheader's body pose during the horizontal cutting process, which seriously influences the positioning and orienting excavation of the roadheader and leads to reduction in forming quality and drivage efficiency of the roadway [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%